Namūżaju al Barāmiji li Ta’līmi al ‘Arabiyyati li Aghrāḍin Mihniyyatin - Mutholib, Abdul (Al-Uslub: Journal of Arabic Linguistic and Literature, 2021)
This paper aims to provide a model for programs to teach Arabic for professional purposes. The paper is exposed to the concept of teaching Arabic for professional purposes. Its characteristics, linguistic needs and the topics studied in it. Some of the pilot programs for teaching Arabic for professional purposes are Arabic language education for pilots, media professionals, doctors and nurses, oil companies, economists, etc. The topics studied in teaching Arabic for professional purposes focus on the vocabulary and expressions required to communicate effectively in business, topics from the language of a specific profession. Therefore, this paper proposes to universities or educational institutions that teach Arabic for professional purposes to focus on achieving educational purposes in providing the learner with competencies, skills and proficiencies that make him able to specialize in the subject of his or her field of work, integrated into his professional environment